Management of the quality of the health-care: Clinical and ethical aspects - D'Ugo, D.; Cambieri, A.; Mascellari, L.; Berloco, F. (Medicina e Morale, 1996)
One of the most frequent topics of discussion in clinical and public health medicine is the difficulty to guarantee high quality levels in hospital and outpatients care and - at the same time - to contain the constantly increasing costs. The Italian National Health Service - as it happens in most Western countries - is now deeply involved in this field, but the information and training levels of health care professionals seems - so far - inadequate to the task. However, studies concerning a more rational use of financial resources are more frequent than in the past. Among them, the appropriateness of hospital admissions is a recurrent theme. The Authors analyze the possible new fields of intervention, strongly encouraged by the recently approved "DRGs-based" prospective payment system for italian hospitals and by the shortly incoming "hospital accreditation" legislation. Finally, the matter is analyzed from the point of view of personalistic bioethics.